2020
DOI: 10.1097/oi9.0000000000000089
|View full text |Cite
|
Sign up to set email alerts
|

Expedited surgery in geriatric hip fracture patients taking direct oral anticoagulants is not associated with increased short-term complications or mortality rates

Abstract: Objectives: The purpose of this study was to evaluate potential differences in time to surgery, bleeding risk, wound complications, length of stay, transfusion rate, and 30-day mortality between patients anticoagulated with direct oral anticoagulants (DOACs) and those not anticoagulated at the time of evaluation for an acute hip fracture. Design: Retrospective chart review Level III Study. Setting: One university-based hospital in Rochester, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Multiple recent studies challenge this idea, with no difference found in transfusion rates and postsurgical hemoglobin changes between patients on DOACs and propensity-matched, uncoagulated cohorts. 30-33 We conclude that there is little evidence supporting routine delay for hip fracture fixation because of DOACs. Based on these studies, the harm from delaying surgery >24 to 48 hours may be greater than the risk of increased perisurgical bleeding from DOAC therapy.…”
Section: Intraoperative Managementmentioning
confidence: 78%
“…Multiple recent studies challenge this idea, with no difference found in transfusion rates and postsurgical hemoglobin changes between patients on DOACs and propensity-matched, uncoagulated cohorts. 30-33 We conclude that there is little evidence supporting routine delay for hip fracture fixation because of DOACs. Based on these studies, the harm from delaying surgery >24 to 48 hours may be greater than the risk of increased perisurgical bleeding from DOAC therapy.…”
Section: Intraoperative Managementmentioning
confidence: 78%
“…Another study, which showed the largest discrepancy between the proportion of DOAC patients operated on after 48 hcompared with non-anticoagulated patients (48.9% DOAC vs 8% nonanticoagulated), also showed no difference in in-hospital or 1-ear mortality between groups (33). Multiple other studies, including a systematic review of 39 446 patients, have shown similar findings of no increased mortality risk associated with delayed surgery in DOAC users (28,29,32,34,36,37,38).…”
Section: Mortality Consequences Of Delayed Time To Surgery In Patient...mentioning
confidence: 79%
“…There was no evidence to indicate if hip fracture surgery for patients taking DOACs could reasonably be delayed, including for different types of hip fracture surgery. Sixteen retrospective cohort [22, 39–53] and four case–control studies [54–57] report the type of hip fracture surgery performed for patients taking DOACs.…”
Section: Resultsmentioning
confidence: 99%